Pengaruh Leverage, Profitabilias, Dan Likuiditasterhadap Nilai Perusahaan (Studi Empiris Perusahaan Perbankan Di Bei 2022 - 2024) - Difa Salsabila Fakhrunnisa; Lukman Effendy (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to examine the effect of leverage, profitability, and liquidity on firm value in banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employs a quantitative approach using multiple linear regression analysis. The population of this study consists of all banking companies listed on the Indonesia Stock Exchange, while the sampling technique uses purposive sampling, resulting in 138 observations during the research period. Leverage is proxied by Debt to Equity Ratio (DER), profitability by Return on Assets (ROA), liquidity by Current Ratio (CR), and firm value by Price to Book Value (PBV). The results indicate that partially leverage, profitability, and liquidity do not have a significant effect on firm value. These findings suggest that firm value in the banking sector is not only influenced by internal financial ratios but may also be affected by other factors such as macroeconomic conditions, monetary policy, and investor confidence in the banking industry.